Pengaruh Pendidikan Kewirausahaan terhadap Kreativitas Mahasiswa Pendidikan Ekonomi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The study aims to determine whether there is an influence of entrepreneurship education on student creativity. This study uses a descriptive quantitative approach with a sample size of 36 people. The instruments used are questionnaires and questionnaires. The data analysis technique used is simple linear regression analysis. Based on the results of the data analysis, it is known that there is a significant influence of entrepreneurship education on the creativity of students of the Department of Economic Education, Faculty of Economics and Business, Gorontalo State University. The magnitude of the influence of entrepreneurship education on student creativity is 62.5% and the remaining 37% is influenced by other variables not examined in this study.